'How did he say that?' interpreting students' written reflections on interprofessional education scenarios with speech language therapists. Issue 1 (2nd January 2022) - Crezee, Ineke; Marianacci, Agustina
ABSTRACT: The project aimed to explore what interpreting students' written reflections reveal about the impact of Interprofessional Education (IPE) on their development as future practising professionals. Student health interpreters from the Auckland University of Technology and postgraduate Speech Science students from the University of Auckland, who were already registered speech and language therapists (SLTs), had a shared 3-hour interprofessional education session which involved semi-authentic role play scenarios. Student healthcare interpreters took turns taking on the role of interpreter or client, while SLTs conducted assessment sessions as they normally would. Scenarios involved a child with language delay accompanied by a parent, and an elderly adult being assessed following a stroke. Student health interpreters reflected on the experience in written reflective assignments which were thematically analysed and coded into five main themes using NVivo software.) Student reflections showed that they had found the experience very beneficial, with comments focusing on the interpreters' code of ethics; understanding each other's roles and how these differ in the SLT context; collaboration between professionals; competence; and the importance of practice for problem-solving.